Platform for therapeutic effect by using a mechanical device designed to evaluate the flat foot is flexible and the development of some motor skills - hade, hussen (Journal of Physical Education, 2010)
The perfect bodily of children is very important issue for society’s health generally and children’s health specially because of their desire to achieve their hops or dreams by participate in football schools which its aims to prepare players for clubs or teams in future , but step by step we are discover these players suffer from Posture Deformities effective on the progress continue of their players’ such as Flexible Flatfoot , so our study focused on prepared therapeutic program in accordance with scientific principles and it is assessment by professionals , this program depend on technical Apparatus so as to meliorate of the flexible flatfoot to many Children simple during 12 weeks and after that the researcher got the positive effective about their flexible flatfoot Which Lead to an increase their dynamic abilities .